2017
DOI: 10.1088/1741-4326/aa82c8
|View full text |Cite
|
Sign up to set email alerts
|

Blister formation on rough and technical tungsten surfaces exposed to deuterium plasma

Abstract: Up to now, blister formation on rough or technical tungsten surfaces exposed to hydrogen isotope plasma was believed to be completely suppressed. The few dedicated experiments on this issue that can be found in literature appear to support that claim. Using a novel technique of three-dimensional difference imaging of tungsten surfaces, we now demonstrate that roughness introduced by chemical etching, i.e., without the associated mechanical deformation layer introduced by grinding, only moderately reduces blist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…In addition, the sample is hit by a flux of low-energy neutral D atoms, which is estimated to be of the order of 100 times higher than the deuteron flux originating from ions. Recent measurements using a retarding field analyzer and a moveable Langmuir probe measuring the ion saturation current j sat indicated that the ion flux was about 20% higher than reported in [11,12] after exchanging the Al 2 O 3 window through which the microwave radiation is transmitted into the vacuum vessel, i.e., the flux is now about 1.2x10 20 D/m 2 s . Repeated Langmuir probe profiles showed only minimal variations between the individual plasma discharges during which Sn samples were exposed.…”
Section: Plasma Exposurementioning
confidence: 88%
“…In addition, the sample is hit by a flux of low-energy neutral D atoms, which is estimated to be of the order of 100 times higher than the deuteron flux originating from ions. Recent measurements using a retarding field analyzer and a moveable Langmuir probe measuring the ion saturation current j sat indicated that the ion flux was about 20% higher than reported in [11,12] after exchanging the Al 2 O 3 window through which the microwave radiation is transmitted into the vacuum vessel, i.e., the flux is now about 1.2x10 20 D/m 2 s . Repeated Langmuir probe profiles showed only minimal variations between the individual plasma discharges during which Sn samples were exposed.…”
Section: Plasma Exposurementioning
confidence: 88%
“…At the same time, the presence of hydrogen in tungsten can also affect the tungsten microstructure. For example, it has been shown that the sub-surface defect structure of tungsten can be modified by deuterium-plasma exposure even far beyond the implantation range [4,8,9]. Defect creation by hydrogen and the effect of defects on the hydrogen distribution in tungsten can lead to a complex interplay [6].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively large blisters (> 5 μm) were visible in low dose (0.025 dpa) neutron-irradiated PCW exposed to similar D plasma conditions [30]. The reduction of blister formation might be due to the crystal orientation and/or the use of rough and technical surfaces of the SCW specimens [11,12]. Ratios of the total D retention obtained by TDS and the near-surface D retention by NRA were more than 5 for the 0.1 dpa neutron-irradiated SCW exposed at the temperature above 673K, indicating plasma-induced near-surface defects do not play a critical role in D/T retention in neutron-irradiated SCW exposed at elevated temperature.…”
Section: Discussionmentioning
confidence: 96%
“…These specimens do not have perfect mirror-finished conditions often used for laboratory experiments, but they represent realistic technical surfaces of the PFCs for future fusion reactors. The effects of rough or technical surfaces on D retention, surface morphologies and blister formation in tungsten were investigated, and reductions of D retention and blister formation near surface were reported in tungsten [11,12]. In this work the effect of technical surfaces on D retention is examined with an unirradiated single crystal tungsten specimen prepared in a similar procedure.…”
Section: Experiments 21 Materials Selectionmentioning
confidence: 99%